Gambaran Gejala Depresi pada Ibu Hamil di Kota Pekanbaru - Khoiriah Nst; Misrawati; Jumaini (STIKes Payung Negeri Pekanbaru, 2022)
Pregnancy is an event that can cause stress. Instantaneous hormonal changes can trigger the occurrence of biochemical depression in pregnant women. This study aims to see the picture of depressive symptoms in pregnant women. This research is descriptive quantitative using a cross sectional approach. The sampling technique in this study used purposive sampling with a total sample of 97 respondents. Data collection techniques using the Edinburgh Postpartum/Perinatal Depression Scale (EPDS) questionnaire. The results of the study with 97 respondents obtained a picture of mothers who experienced the incidence of depressive symptoms during pregnancy totaling 17 respondents (17.5%) and depressive symptoms felt by pregnant women in this study with the majority of mothers often feeling unhappy so it was difficult to sleep 9 respondents (52.9%), mothers often felt worried or had palpitations for no reason 9 respondents (52.9%), sometimes -sometimes mothers blame themselves if something doesn't go well 8 respondents (47.1%) and mothers rarely feel sad or difficult 8 respondents (47.1%) and mothers never think of harming themselves 17 respondents (100 %). During pregnancy, the mother can experience depressive symptoms, during pregnancy it is important to do screening to prevent depression which will have a detrimental impact on the mother and fetus if left untreated.